2020
DOI: 10.3847/1538-4365/ab86af
|View full text |Cite
|
Sign up to set email alerts
|

Parker Solar Probe Observations of Proton Beams Simultaneous with Ion-scale Waves

Abstract: Parker Solar Probe (PSP), NASA's latest and closest mission to the Sun, is on a journey to investigate fundamental enigmas of the inner heliosphere. This paper reports initial observations made by the Solar Probe Analyzer for Ions (SPAN-I), one of the instruments in the Solar Wind Electrons Alphas and Protons (SWEAP) instrument suite. We address the presence of secondary proton beams in concert with ion-scale waves observed by FIELDS, the electromagnetic fields instrument suite. We show two events from PSP's 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(118 citation statements)
references
References 91 publications
9
109
0
Order By: Relevance
“…This combined plasma and magnetic field signature of a patch is the main result of this letter. Overall, T p,⊥ > T p, throughout the interval, which is consistent with many observations of fast wind in the inner heliosphere (Ďurovcová et al 2019;Hellinger et al 2011Hellinger et al , 2013Marsch et al 1981Marsch et al , 1982Marsch et al , 2004Matteini et al 2007;Perrone et al 2019a,b;Stansby et al 2019aStansby et al ,b, 2020 and the recent analysis of slow Alfvénic wind observed by PSP (Huang et al 2020a,b;Verniero et al 2020). In addition, we see in panel (5) that patches sometimes display small density enhancements in both n p and n e .…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This combined plasma and magnetic field signature of a patch is the main result of this letter. Overall, T p,⊥ > T p, throughout the interval, which is consistent with many observations of fast wind in the inner heliosphere (Ďurovcová et al 2019;Hellinger et al 2011Hellinger et al , 2013Marsch et al 1981Marsch et al , 1982Marsch et al , 2004Matteini et al 2007;Perrone et al 2019a,b;Stansby et al 2019aStansby et al ,b, 2020 and the recent analysis of slow Alfvénic wind observed by PSP (Huang et al 2020a,b;Verniero et al 2020). In addition, we see in panel (5) that patches sometimes display small density enhancements in both n p and n e .…”
Section: Resultssupporting
confidence: 84%
“…Proton VDFs measured by SPAN-Ai often show the presence of both a proton core and a field-aligned beam; a second proton component that streams faster than the core along the direction ofb = B/|B| (see Verniero et al 2020). In Figure 1, we show a typical distribution measured by SPAN-Ai in the instrument frame 1 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Correlations between signatures of the transition range and parameters associated with stochastic heating were not found [42,63]. Measurements of 3D ion distributions will enable comparison of damping rates associated with, e.g., Landau and cyclotron resonance, with our observed dissipation rates [1,8,[10][11][12][13][14]17,18,76,82,83]. Additionally, heating processes may leave clear signatures in the distribution function: e.g., diffusive shells in the case of cyclotron resonance [84] or flattening associated with resonant damping or perpendicular stochastic heating [63,85].…”
mentioning
confidence: 84%